2019
DOI: 10.5606/archrheumatol.2019.7111
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Risk Factors and Assessment of Depressive Symptoms in Patients With Systemic Sclerosis

Abstract: Objectives: This study aims to evaluate the prevalence of depressive symptoms among systemic sclerosis (SSc) patients using the Major Depression Inventory (MDI), identify possible risk factors, and analyze the current standard of care to raise awareness and improve clinical care for SSc patients. Patients and methods: The study included 94 SSc patients (12 males, 82 females; mean age 58.3±13.6 years; range, 28 to 83 years) who completed the MDI, Short Form 36 Health Survey, Scleroderma Health Assessment Questi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 29 publications
1
11
0
Order By: Relevance
“…The results of our Delphi study showed that, according to the panellists, most SSc-ILD patients suffer from a number of comorbidities, such as gastroesophageal reflux disease (53.8%), fatigue (40.3%) or depression (22.6%). These results are consistent with the reports in the literature for SSc or SSc-ILD patients [32][33][34].…”
Section: Management and Social Burdensupporting
confidence: 93%
“…The results of our Delphi study showed that, according to the panellists, most SSc-ILD patients suffer from a number of comorbidities, such as gastroesophageal reflux disease (53.8%), fatigue (40.3%) or depression (22.6%). These results are consistent with the reports in the literature for SSc or SSc-ILD patients [32][33][34].…”
Section: Management and Social Burdensupporting
confidence: 93%
“…Depressive symptoms are associated with poor HRQL [ 8 ]. Patients with SSc who have depressive symptoms are also reported to be less physically active than those without depressive symptoms [ 9 ]. Further, depressive symptoms are associated with lower self-efficacy and reduced likelihood of adopting health-promoting behaviors [ 6 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…At no point in our study did we claim that we assessed the prevalence of depression in SSc. 1 You might be right that the scientific value of estimating the prevalence of MDI-relevant items is limited. However, as we mention in the discussion of our paper, we want to raise the awareness for mental health issues in SSc without providing psychiatric diagnoses, measuring significant impairment or estimating the prevalence of depressive disorders in SSc.…”
mentioning
confidence: 99%